2000
DOI: 10.1074/jbc.275.3.1587
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillatory Behavior of Pancreatic Islets from Mice with Mitochondrial Glycerol-3-phosphate Dehydrogenase Knockout

Abstract: ] i on the exocytotic process (6 -8). Both pathways require glucose metabolism and appear to depend on a rise in the ATP/ADP ratio (9).Glucose metabolism in ␤ cells essentially occurs through aerobic glycolysis (10 -12). An increase in the glucose concentration is followed by an acceleration of glycolysis and an even greater stimulation of mitochondrial oxidative events, in which Ca 2ϩ may play an important role. Thus, the elevation of [Ca 2ϩ ] i is paralleled by an increase in mitochondrial Ca 2ϩ (13) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
3
24
1
Order By: Relevance
“…Mitochondrial glycerol-3-phosphate dehdyrogenase. Islets from mutant mice that lack mitochondrial glycerol-3-phosphate dehydrogenase activity have normal glucosestimulated insulin release (56,65). This is consistent with the succinate mechanism, which does not require an intact glycerol-3-phosphate shuttle for glucose-stimulated insulin release.…”
Section: Regulatory Features Of the Succinate Mechanismsupporting
confidence: 66%
“…Mitochondrial glycerol-3-phosphate dehdyrogenase. Islets from mutant mice that lack mitochondrial glycerol-3-phosphate dehydrogenase activity have normal glucosestimulated insulin release (56,65). This is consistent with the succinate mechanism, which does not require an intact glycerol-3-phosphate shuttle for glucose-stimulated insulin release.…”
Section: Regulatory Features Of the Succinate Mechanismsupporting
confidence: 66%
“…Although several previous reports have described mGPDH -/-mice as normal [14,15,16,17], our results showed that the blood concentrations of triglycerides and cholesterol in mGPDH -/-mice are increased. These results could be due to the absence of mGPDH activity in the liver, but not in the pancreas.…”
Section: Discussioncontrasting
confidence: 99%
“…To determine the role of the glycerol-3-phosphate shuttle in glucose-induced insulin secretion, mice with a targeted disruption of the mGPDH gene were generated [14,15]. mGPDH -/-knockout mice are not diabetic, only when the activities of both shuttles are halted by the use of aminooxyacetate, to block the malate-aspartate shuttle, are insulin secretion, glucose metabolism, and calcium oscillations severely impaired [16,17].…”
mentioning
confidence: 99%
“…The numerous islets composing the endocrine pancreas could be functionally heterogeneous, some of them being responsible for the first phase and others for the second phase (6). This hypothesis is refuted by the observation of biphasic insulin secretion from single islets (7)(8)(9)(10). Another possibility is that, within each islet, different ␤-cells preferentially secrete during first or second phase.…”
mentioning
confidence: 82%